Profil Keterampilan Komunikasi dan Kolaborasi Peserta Didik dalam Pembelaran IPA Materi Pengenalan Sel pada Siswa SMP - Hasanah, Lia Al; Hasruddin, Hasruddin (Lembaga Yasin AlSys, 2024)
This study aims to determine the profile of communication and collaboration skills of students in science learning on cell recognition material in class VIII SMP Negeri 8 Medan based on indicators of communication and collaboration skills and also based on the results of observations in learning and the results of in-depth interviews with students. This research was conducted in April-August 2024 at SMP Negeri 8 Medan. This research is included in descriptive research with qualitative methods. Determination of subjects using purposive sampling technique. The subjects consisted of 1 science teacher of class VIII and 4 students of class VIII. The data analysis technique used in this research is descriptive qualitative. Data were collected through in-depth interviews with research subjects and also direct observation related to communication and collaboration skills of students in learning. The results showed that the communication and collaboration skills of students on cell recognition material showed diverse abilities. The observation showed that only some students were active in sharing their opinions during class discussions, while others were not able to explain the material well. Although students' enthusiasm was high, only a few were able to effectively discuss the material again. However, they showed good communication by asking and answering questions from the teacher and classmates. In addition, students' collaboration skills can be seen from active participation in discussions and group work, where they can work together to complete tasks in a timely and responsible manner.